Minichromosome maintenance helicase paralog MCM9 is dispensible for DNA replication but functions in germ-line stem cells and tumor suppression - Suzanne A. Hartford; Yunhai Luo; Teresa Southard; Irene M. Min; John T. Lis; John C. Schimenti (2011)
Effective DNA replication is critical to the health and reproductive success of organisms. The six MCM2–7 proteins, which form the replicative helicase, are essential for high-fidelity replication of the genome. Many eukaryotes have a divergent paralog, MCM9, that was reported to be essential for loading MCM2–7 onto replication origins in the Xenopus oocyte extract system. To address the in vivo role of mammalian MCM9, we created and analyzed the phenotypes of mice with various mutations in Mcm9 and an intronic DNA replication-related gene Asf1a . Ablation of Mcm9 was compatible with cell proliferation and mouse viability, showing that it is nonessential for MCM2–7 loading or DNA replication. Mcm9 mutants underwent p53-independent embryonic germ-cell depletion in both sexes, with males also exhibiting defective spermatogonial stem-cell renewal. MCM9-deficient cells had elevated genomic instability and defective cell cycle reentry following replication stress, and mutant animals were prone to sex-specific cancers, most notably hepatocellular carcinoma in males. The phenotypes of mutant mice and cells suggest that MCM9 evolved a specialized but nonessential role in DNA replication or replication-linked quality-control mechanisms that are especially important for germ-line stem cells, and also for tumor suppression and genome maintenance in the soma.